Time and the other : how anthropology makes its object - Fabian, Johannes; Bunzl, Matti (New York : Columbia University Press, 2002)
Foreword to Johannes Fabian's Time and the Other: Syntheses of a Critical Anthropology/by Matti Bunzl ##Preface to the Reprint Edition ##Preface and Acknowledgments ## ##Chapter 1: Time and the Emerging Other ##- From Sacred to Secular Time: The Philosophical Traveler ##- From History to Evolution: The Naturalization of Time ##- Some Uses of Time in Anthropological Discourse ##- Taking Stock: Anthropological Discourse and Denial of Coevalness## ##Chapter 2: Our Time, Their Time, No Time: Coevalness Denied ##- Circumventing Coevalness: Cultural Relativity ##- Preempting Coevalness: Cultural Taxonomy ## ##Chapter 3: Time and Writing About the Other ##- Contradiction: Real or Apparent ##- Temporalization: Means or End? ##- Time and Tense: The Ethnographic Present ##- In My Time: Ethnography and the Autobiographic Past ##- Politics of Time: The Temporal Wolf in Taxonomic Sheep's Clothing ## ##Chapter 4: The Other and the Eye: Time and the Rhetoric of Vision ##- Method and Vision ##- Space and Memory ##- Logic as Arrangement: Knowledge Visible ##- Vide et Impera: The Other as Object ##- "The Symbol Belongs to the 0rient": Symbolic Anthropology in Hegel's Aesthetic ##- The Other as Icon: The Case of "Symbolic Anthropology' ## ##Chapter 5: Conclusions ##- Retrospect and Summary ##- Issues for Debate ##- Coevalness: Points of departure.
Onderzoek KASK (1KA-OFBG)
boek